Public versus private investment multipliers in emerging market and developing economies: Cross-country analysis with a focus on Asia - Jo\~ao Tovar Jalles; Donghyun Park; Irfan A. Qureshi (Asian Development Bank (ADB), 2024)
This paper analyzes the growth impact of public and private investment shocks based on a large sample of emerging and developing countries over the period 1980-2021 with a particular focus on the Asian region. We develop new measures of investment shocks based on cyclically adjusted investment data. Estimations using local projections suggest that public investment shocks play a much greater role in boosting economic growth in comparison with private investment shocks. In emerging market and developing economies (EMDEs) (including in Asia), the growth response to investment shocks is positive and much stronger in recessions relative to economic expansions. Finally, public investment shocks in EMDE and Asian samples crowd-in private investment and private consumption.
Keywords: C33; E22; H30; H50; 330; fiscal multipliers; public investment; private investment